DIGITAL TRANSFORMATION OF NABATI POETRY: REMEDIATION, AUDIENCE ROLE, AND AUTHENTICITY NEGOTIATION - Syaifullah Syaifullah; Ahdiyat Mahendra; Khasanah Khasanah (CMES (Center of Middle Eastern Studies), 2026)
This study examines how Nabati Poetry is transformed within the digital ecosystem of TikTok. The research explores the ways in which poetic structure adapts to the platform’s logics, the role of audiences in shaping contemporary popular literary practices, and the negotiation of authenticity within participatory digital spaces. Employing a multimodal digital ethnography approach combined with qualitative content analysis, six TikTok videos featuring Nabati Poetry published between 2020 and 2025 were purposively selected based on audience engagement and thematic richness. The findings reveal that structural adaptation occurs through compressed verses, heightened emotional intensity, and expressive visuality in order to align with TikTok’s algorithmic dynamics. Audiences emerge not merely as passive recipients but as value curators, actively shaping performative norms and determining the visibility of poetic content. Authenticity, moreover, is shown to be negotiated not only through adherence to classical forms but also through cultural resonance, visual strategies, and participatory relevance. This study contributes to Arabic digital literary studies by demonstrating how platform cultures reshape oral traditions through remediation, audience agency, and sociotechnical aesthetics.